Pageantry and Power A Cultural History of the Early Modern Lord Mayor's Show 1585-1639 - Hill, Tracey (Manchester University Press, 2011)
Pageantry and Power is the first full and in-depth cultural history of the Lord Mayor's Show in the early modern period. It provides new insight into the culture and history of the London of Shakespeare's time and beyond.Central to the cultural life of London, the Lord Mayor's Shows were high-profile and lavish entertainments produced by some of the most talented writers of the time. Employing an interdisciplinary approach, Pageantry and Power explores various important factors, including the relationship between the printed texts of the Shows and actual events.This full-scale study of the civic works of important writers enhances our understanding of their other, often better-known, dramatic works contributing to a fuller estimation of their literary careers.This book is an invaluable resource for scholars and students of early modern literature, drama, history, civic culture, pageantry, urban studies, cultural geography, book history, as well as the interested general reader.